VD_FINDINFO Pron / 2009 / 27 vom 21. August 2009 - VD Tribunal cantonal (2009)
DÉCISION D'IRRECEVABILITÉ, MESURE PROVISIONNELLE, EFFET SUSPENSIF, OBJET DU RECOURS | 108 al. 1 CPC, 112 al. 4 CPC, 443 al. 1 CPC